2022
DOI: 10.1177/20503245221119046
|View full text |Cite
|
Sign up to set email alerts
|

How to read a paper on the short-term impairing effects of cannabis: A selective and critical review of the literature

Abstract: The prosecution of cannabis-presence driving offences (in the absence of any behavioural evidence of impairment) is ultimately based on the assumption that there is a tight causal relationship between positive toxicology for cannabis and impairment. The main purpose of this review is to examine the evidence for that relationship. We show that most experimental studies have failed to elicit statistically-significant cannabis-induced impairments for many of their possible outcomes. And many studies failed to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…The degree of impairment resulting from cannabis use is clearly related to the dosage administered (e.g., Schlienz et al, 2020). However, that relationship does not seem to translate into demonstrable dose-response relationship between the concentration of THC in the blood or oral fluid and either the level of impairment (Arkell et al, 2021; White and Burns, 2022b: 16-18; Wurz and DeGregorio, 2022) or the risk of crashing (Macdonald, 2018: 96; White and Burns, 2021: 12-13). Nevertheless, it is certainly possible to get so intoxicated on cannabis that one is incapable of safely driving a car.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of impairment resulting from cannabis use is clearly related to the dosage administered (e.g., Schlienz et al, 2020). However, that relationship does not seem to translate into demonstrable dose-response relationship between the concentration of THC in the blood or oral fluid and either the level of impairment (Arkell et al, 2021; White and Burns, 2022b: 16-18; Wurz and DeGregorio, 2022) or the risk of crashing (Macdonald, 2018: 96; White and Burns, 2021: 12-13). Nevertheless, it is certainly possible to get so intoxicated on cannabis that one is incapable of safely driving a car.…”
Section: Discussionmentioning
confidence: 99%
“…However, they note that skewed, agenda-driven reporting has undermined this area of inquiry. Finally, in a recent analysis of experimental studies on cannabis impairment and driving, White and Burns (2022) found that many of the existing studies have "failed to demonstrate any impairment at all in regular users of cannabis" (pg. 1).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…6 Driving a vehicle immediately after cannabis use is associated with a low to medium increased risk of crashes 8 due to impaired cognitive abilities. [9][10][11] However, it should be noted that the evidence is found to be inconsistent, 12 possibly due to methodological biases, compensatory mechanisms and development of tolerance among some drivers. [12][13][14] Both CUD and (self-reported) DUIC are especially…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, it should be noted that the evidence is found to be inconsistent, 12 possibly due to methodological biases, compensatory mechanisms and development of tolerance among some drivers. [12][13][14] Both CUD and (self-reported) DUIC are especially…”
Section: Introductionmentioning
confidence: 99%